Analisis Penerapan Aplikasi Catatan Keuangan Pada Laporan Keuangan Umkm Toko Beras Farida, Karawang - Syahdena Nur Awalia; Rohma Septiawati; Awaliawati Rachpriliani (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study aims to analyze the application of Android-based Financial Records application in the preparation of financial statements in MSMEs of Farida Rice Shop in Karawang, as well as assess its suitability with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). The method in this study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The findings of his research show that the implementation of the Financial Records application simplifies the recording process, speeds up the preparation of reports, and reduces the risk of calculation errors. However, this application does not fully meet the SAK EMKM format, so manual adjustments are required. Supporting factors for implementation include ease of use of the application and local government support, while inhibiting factors include limited features and lack of accounting literacy of business actors. This study recommends intensive training for UMKM actors to be able to take advantage of the application.